ΣΠΑΡΑΓΜΟΣ y cefaloforía en Las Bacantes y Las Dionisíacas: El mito de Penteo en Eurípides y Nono - Hernández de la Fuente, david alejandro (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2001)
the folowing essay deals with the different aproach to the myth of panteius and the bacchae in two authors,euripides,a clasical tragedy writer,and nannus of panopolis, a late greek-egypctian epic poet. the story of pantheus in nonnus dionysiaca is based upon euripides bacchae , but there are some outstanding variations. the iconography of this myth can be traced also in euripides and nonnus narrantions which weshall analize through two main mythological episodes: the______ and the exhibition of pantheus head.